Effect of sulfonamide derivatives of phenylglycine on scopolamine‐induced amnesia in rats - Ankit Ganeshpurkar; Ravi Singh; Pratigya Tripathi; Qadir Alam; Sairam Krishnamurthy; Ashok Kumar; Sushil K. Singh (Ibrain, 2023)
Abstract Alzheimer's disease is a neurodegenerative disease responsible for dementia and other neuropsychiatric symptoms. In the present study, compounds 30 and 33, developed earlier in our laboratory as selective butyrylcholinesterase inhibitors, were tested against scopolamine‐induced amnesia to evaluate their pharmacodynamic effect. The efficacy of the compounds was determined by behavioral experiments using the Y‐maze and the Barnes maze and neurochemical testing. Both compounds reduced the effect of scopolamine treatment in the behavioral tasks at a dose of 20 mg/kg. The results of the neurochemical experiment indicated a reduction in cholinesterase activity in the prefrontal cortex and the hippocampus. The levels of antioxidant enzymes superoxide dismutase and catalase were restored compared to the scopolamine‐treated groups. The docking study on rat butyrylcholinesterase (BChE) indicated tight binding, with free energies of −9.66 and −10.23 kcal/mol for compounds 30 and 33, respectively. The two aromatic amide derivatives of 2‐phenyl‐2‐(phenylsulfonamido) acetic acid produced stable complexes with rat BChE in the molecular dynamics investigation.